2021
DOI: 10.1017/s003118202100010x
|View full text |Cite
|
Sign up to set email alerts
|

Know your enemy – transcriptome of myxozoanTetracapsuloides bryosalmonaereveals potential drug targets against proliferative kidney disease in salmonids

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 94 publications
1
19
0
Order By: Relevance
“…In spite of the immune functions of the kidney, T. bryosalmonae can successfully undergo sporogony in the kidney of the affected fish and be released in the urine ( Sudhagar et al., 2019 ; Sudhagar et al., 2020 ) suggesting that this parasite has evolved to survive in an extremely hostile environment by molecular adaption. Most of the previous experiments on brown trout - T. bryosalmonae interactions were conducted to understand the host (brown trout) response ( Kumar et al., 2014 ; Kumar et al., 2015 ; Bailey et al., 2019 ; Sudhagar et al., 2019 ; Sudhagar et al., 2020 ; Shivam et al., 2021 ; Sudhagar et al., 2022 ), while only a few studies focused on generating molecular information on T. bryosalmonae ( Ahmad et al., 2021 ; Faber et al., 2021 ; Kumar et al., 2021 ). Identification of in vivo induced antigens or genes of the parasite during host-pathogen interactions, particularly during its development host, will provide valuable insight into the molecular adaption of the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the immune functions of the kidney, T. bryosalmonae can successfully undergo sporogony in the kidney of the affected fish and be released in the urine ( Sudhagar et al., 2019 ; Sudhagar et al., 2020 ) suggesting that this parasite has evolved to survive in an extremely hostile environment by molecular adaption. Most of the previous experiments on brown trout - T. bryosalmonae interactions were conducted to understand the host (brown trout) response ( Kumar et al., 2014 ; Kumar et al., 2015 ; Bailey et al., 2019 ; Sudhagar et al., 2019 ; Sudhagar et al., 2020 ; Shivam et al., 2021 ; Sudhagar et al., 2022 ), while only a few studies focused on generating molecular information on T. bryosalmonae ( Ahmad et al., 2021 ; Faber et al., 2021 ; Kumar et al., 2021 ). Identification of in vivo induced antigens or genes of the parasite during host-pathogen interactions, particularly during its development host, will provide valuable insight into the molecular adaption of the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…The patterns of expression observed for these cysteine proteases do not exclude the possibility that other cysteine proteases could have important roles in pathogenesis of genotype IIR. The protease repertoire of C. shasta includes other cysteine proteases (Table 2; Alama-Bermejo et al, 2020;Ahmad et al, 2021), which may contribute to the parasite's proteolytic activity on the host intestine extracellular matrix, as reported in other histolytical parasites e.g. Entamoeba histolytica (Kissoon-Singh et al, 2011), where cysteine proteases are primary virulence factors.…”
Section: The Less Virulent Genotype May Use Cysteine Proteases To Evade the Host Immune Systemmentioning
confidence: 97%
“…On the host side, it seems reasonable to deduce that it would be beneficial to prevent the gross tissue damage that occurs with the massive granulomatous inflammation shown in advanced PKD. Recent progress in comparative transcriptomics (Ahmad, Debes, Pukk, et al., 2021; Faber et al., 2021) and genetic profiling of immunity (Bailey, Holland, et al., 2020) is now starting to reveal the extent to which such adaptations have evolved in both parasite and its hosts (Ahmad, Debes, Nousiainen, et al., 2021). In general, such adaptions are expected to result in evolution for low virulence of the parasitic infection and this would fit the hypothesis that proliferation of T. bryosalmonae in the kidney does not result in gross pathology at water temperature conditions that prevailed in salmonid habitat before anthropogenic global warming (Borgwardt et al., 2020; Bruneaux et al., 2017; Lauringson et al., 2021; Strepparava et al., 2018; Wahli et al., 2002).…”
Section: The Relation Between Temperature and Proliferative Kidney Di...mentioning
confidence: 99%
“…This situation might, however, change as recent transcriptome studies have identified promising molecular targets (i.e. endoglycoceramidase, legumain‐like protease, carbonic anhydrase 2 and pancreatic lipase‐related protein 2) that can be used for developing future drugs against T. bryosalmonae infections (Ahmad, Debes, Pukk, et al., 2021; Faber et al., 2021). The main solution for farms with mortalities related to PKD has been to raise the fingerlings using cool spring or mountain water (<15°C; De Kinkelin & Loriot, 2001).…”
Section: Management Options For Mitigating Pkd In Salmonidsmentioning
confidence: 99%
See 1 more Smart Citation